Lupus low disease activity state attainment in the phase 3 TULIP trials of anifrolumab in active systemic lupus erythematosus. Issue 5 (23rd January 2023) - Morand, Eric F; Abreu, Gabriel; Furie, Richard A; Golder, Vera; Tummala, Raj
Abstract : Objectives: In patients with systemic lupus erythematosus (SLE), lupus low disease activity state (LLDAS) attainment is associated with improved outcomes. We investigated LLDAS attainment in anifrolumab-treated patients. Methods: We performed post hoc analysis of pooled Treatment of Uncontrolled Lupus via the Interferon Pathway (TULIP-1) (NCT02446912 ) and TULIP-2 (NCT02446899 ) anifrolumab phase 3 trial data in patients with moderate to severe SLE receiving standard therapy. LLDAS was defined as: SLE Disease Activity Index 2000 ≤4 without major organ activity, no new disease activity, Physician's Global Assessment ≤1, prednisone ≤7.5 mg/day and no non-standard immunosuppressant dosing. Time to first LLDAS attainment was compared between groups using Cox regression modelling; responses were compared using logistic regression. Results: Agnostic to treatment, 205/819 (25.0%) patients attained LLDAS at week 52; 186/205 (90.7%) were also British Isles Lupus Assessment Group-based Composite Lupus Assessment (BICLA)-responders. Among BICLA-responders at week 52, 186/318 (58.5%) attained LLDAS; 203/380 (53.4%) SLE Responder Index-4 (SRI(4)) responders attained LLDAS. Improvements from baseline in patient global assessment scores at week 52 were threefold greater in LLDAS-attainers. At week 52, 30.0% of anifrolumab-treated patients and 19.6% of placebo were in LLDAS (OR 1.8, 95% CI 1.3 to 2.5, p=0.0011). Compared with placebo, anifrolumab treatment was associated with earlier LLDAS attainment (time to first LLDAS, HR 1.76, 95% CI 1.35 to 2.30, p<0.0001), increased cumulative time in LLDAS (p<0.0001) and higher likelihood of sustained LLDAS (p<0.001). Anifrolumab treatment was also associated with higher rates of Definition of Remission in SLE remission at week 52 (15.3% vs 7.6%; OR 2.2, 95% CI 1.4 to 3.6, p=0.0013). Conclusions: LLDAS attainment was highly associated with, but more stringent than, BICLA and SRI(4) responses. Compared with placebo, anifrolumab treatment was associated with earlier, more frequent, and more prolonged and sustained LLDAS. Trial registration numbers: NCT02446912 and NCT02446899 .